Developing and implementing a strategy-driven performance management system in a higher education institution - Santos, Sérgio Pereira dos (2014)
Performance measurement in higher education has become a challenging issue over the past two decades. Increasingly, institutions of higher education have been required to develop performance measurement systems for both external reporting and internal management purposes. Despite this, little research has been documented regarding the application of the Balanced Scorecard in the education sector, especially at the departmental/faculty level. The objective of this paper is to contribute to filling this void by discussing the development of a performance management system, according to the principles of the Balanced Scorecard, in the Faculty of Economics of one of Portugal’s newer universities.